2019
DOI: 10.1002/ecy.2725
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic modification of plants enhances long‐distance dispersal of nonpersistently transmitted viruses to new hosts

Abstract: Aphids spread the majority of plant viruses through nonpersistent transmission (NPT), whereby virus particles attach transiently to these insects’ probing mouthparts. Virus acquisition from infected plants and inoculation to healthy host plants is favored when aphids briefly probe plant epidermal cells. It is well established that NPT virus infection can alter plant–vector interactions, and, moreover, such pathogen modifications are found in a range of plant and animal systems. In particular, viruses can make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 36 publications
0
56
0
Order By: Relevance
“…This appears hampered, especially on virus-infected plants, and the resulting reduced phloem feeding is unfavorable to long term colonization. The ensuing dispersal to more favorable hosts would promote local vectoring of non-persistently transmitted viruses (Donnelly et al, 2019). On plants infected with any of the three viruses, A. fabae experienced mechanical stylet difficulties, whereas these difficulties did not occur on mock-inoculated plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This appears hampered, especially on virus-infected plants, and the resulting reduced phloem feeding is unfavorable to long term colonization. The ensuing dispersal to more favorable hosts would promote local vectoring of non-persistently transmitted viruses (Donnelly et al, 2019). On plants infected with any of the three viruses, A. fabae experienced mechanical stylet difficulties, whereas these difficulties did not occur on mock-inoculated plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in cucurbits and Arabidopsis thaliana, CMV infection causes accumulation of plant metabolites that are distasteful to aphids (Mauck et al, 2010;Westwood et al, 2013). These distasteful compounds deter aphids from settling and encourage their dispersal, which will accelerate virus transmission to plants in the immediate vicinity (Donnelly et al, 2019). EPG measurements showed that aphids on CMV-infected Arabidopsis plants ingested less phloem sap, which would normally be these insects' major nutrition source and aphids confined on these plants grew less well (Westwood et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is well known [10,39,40] that vector-implicit models may reasonably approximate vector-explicit models when vector dynamics can be considered to be fast with respect to epidemiological dynamics in the plant host population (such as in non-persistent transmission). Although see [41] for a different model of non-persistent transmission of viruses that goes beyond differential equations to track the epidemiological effects of vector dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses alter interactions between plants and insect vectors in ways that may promote virus transmission, or which may foster persistence and spread of vectors in the environment (Casteel et al ., , ; Donnelly et al , ; Groen et al , ; Mauck, ). The effects of CMV on plant–aphid interactions are not the same for all plant hosts.…”
Section: Introductionmentioning
confidence: 99%